Enhanced pyroelectric conversion of thermal radiation energy: Energy harvesting and non-contact proximity sensor. (15th June 2022) - Lee, Junho; Kim, Hyeong Jun; Ko, Young Joon; Baek, Jae Yun; Shin, Gilyong; Jeon, Jei Gyeong; Lee, Ju Hwan; Kim, Ju Hyeon; Jung, Jong Hoon; Kang, Tae June
Abstract: Pyroelectric generators convert temperature fluctuations into useful electrical energy. We introduce here tosylate-doped poly(3, 4-ethylenedioxythiophene) (PEDOT:Tos) as a high-performance, thermal radiation absorbing electrode for polyvinylidene difluoride, a pyroelectric material of choice among flexible polymers. With the PEDOT:Tos electrode prepared by the optimal conditions established, a significant improvement in the device efficiency is realized that is anywhere between severalfold and an order of magnitude, when compared with metal and other organic electrodes. An effectiveness factor is derived and utilized here for the comparison. The fabricated pyroelectric device is utilized to charge a commercial capacitor to demonstrate thermal energy harvest. This device with PEDOT:Tos is highly sensitive to thermal radiation, producing a high voltage in response to thermal energy. This noticeable feature is utilized to demonstrate a non-contact pyroelectric proximity sensor that is powered by a finger approaching the sensor. These results bode well for the applicability of this work to self-powered devices and electronic sensors operated with thermal radiation sources. Graphical Abstract: ga1 Highlights: Introduction of thermal radiation-absorbing PEDOT:Tos electrode material for PVDF-based pyroelectric generator. Up to an order of magnitude improvement in the energy conversion efficiency with the electrode. Introduction of a measure of performance of the device efficiency of converting thermal energy to electrical energy. Demonstration of pyroelectric energy storage by the device. Presentation of a non-contact proximity sensor.